PENERAPAN MEDIA POWERPOINT UNTUK MENINGKATKAN HASIL BELAJAR SISWA KELAS IV - Rizky Yogie Aristianto; Ika Septiani; Elis Dwi Purbiyanti (Universitas Negeri Medan, 2021)
Abstract: This study aims to determine the improvement of fourth grade students' learning outcomes using power point media. The form of this research is this research is CAR (Classroom Action Research). This research was carried out for 6 meetings, where each meeting was 2x35 minutes. Data collection techniques in this study used tests, observations, and documentation. Based on the research, student learning outcomes have increased from the initial conditions or pre-cycle to cycle I, to cycle II and cycle III. This can be proven by the achievement of mastery learning outcomes in the pre-cycle, which is 47% of students who get a complete score with an average of 64. In the first cycle, it increases to 63% of students who get a complete score with an average of 70. Then in the second cycle increased to reach 79% of students got a complete score with an average of 78 class. Furthermore, in the third cycle increased to 89% of students got a complete score with an average of 82 class. Keywords: Application, Power Point Media, Learning OutcomesAbstrak: Penelitian ini bertujuan untuk mengetahui peningkatan hasil belajar siswa kelas IV menggunakan media power point. Bentuk penelitian ini adalah penelitian ini adalah PTK (Penelitian Tindakan Kelas). Penelitian ini dilaksanakan selama 6 pertemuan, dimana setiap pertemuan selama 2x35 menit. Teknik pengumpulan data dalam penelitian ini menggunakan tes, observasi, dan dokumentasi. Berdasarkan penelitian, hasil belajar peserta didik mengalami peningkatan dari kondisi awal atau pra siklus ke siklus I, ke siklus II dan siklus III. Hal ini dapat dibuktikan dengan ketercapaian ketuntasan hasil belajar pada pra siklus yaitu 47 % peserta didik mendapat nilai tuntas dengan rata-rata kelas 64. Pada siklus I meningkat mencapai 63% peserta didik mendapat nilai tuntas dengan rata-rata kelas 70. Kemudian pada siklus II meningkat mencapai 79% peserta didik mendapat nilai tuntas dengan rata-rata kelas 78. Selanjutnya pada siklus III meningkat mencapai 89% peserta didik mendapat nilai tuntas dengan rata-rata kelas 82.Kata Kunci: Penerapan, Media Power Point, Hasil Belajar.